2021
DOI: 10.1016/j.jbc.2021.100260
|View full text |Cite
|
Sign up to set email alerts
|

1,6-Hexanediol, commonly used to dissolve liquid–liquid phase separated condensates, directly impairs kinase and phosphatase activities

Abstract: The concept of liquid–liquid phase separation (LLPS) has emerged as an intriguing mechanism for the organization of membraneless compartments in cells. The alcohol 1,6-hexanediol is widely used as a control to dissolve LLPS assemblies in phase separation studies in diverse fields. However, little is known about potential side effects of 1,6-hexanediol, which could compromise data interpretation and mislead the scientific debate. To examine this issue, we analyzed the effect of 1,6-hexanediol on the activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 56 publications
(71 reference statements)
2
69
0
Order By: Relevance
“…IF analysis showed that MS023 treatment induces cytosolic aggregates in which the proteins under investigation co-localize with both G3BP1 and EU-labelled RNA ( Figure 6B and Supplementary Figure S4A , respectively); such aggregates were overall not observed (or detected to a much lower extenet) when cells were treated with either DMSO or GSK591. Remarkably, MS023-induced granules were disassembled upon treatment with 1,6-Hexanediol, an alcohol widely used for solubilisation of MLOs ( Duster et al, 2021 ), which confirms the phase-separation origin of these RNPs. As further control, we also profiled the subcellular localization of LDHB and 14-3-3 proteins upon NaAsO 2 , a compound well-known to induce SGs formation: as expected, stronger and more numerous G3BP1-stained MLOs were formed upon NaAsO 2 treament, which remarkably displayed co-localization with our proteins of interest and RNA.…”
Section: Resultsmentioning
confidence: 60%
“…IF analysis showed that MS023 treatment induces cytosolic aggregates in which the proteins under investigation co-localize with both G3BP1 and EU-labelled RNA ( Figure 6B and Supplementary Figure S4A , respectively); such aggregates were overall not observed (or detected to a much lower extenet) when cells were treated with either DMSO or GSK591. Remarkably, MS023-induced granules were disassembled upon treatment with 1,6-Hexanediol, an alcohol widely used for solubilisation of MLOs ( Duster et al, 2021 ), which confirms the phase-separation origin of these RNPs. As further control, we also profiled the subcellular localization of LDHB and 14-3-3 proteins upon NaAsO 2 , a compound well-known to induce SGs formation: as expected, stronger and more numerous G3BP1-stained MLOs were formed upon NaAsO 2 treament, which remarkably displayed co-localization with our proteins of interest and RNA.…”
Section: Resultsmentioning
confidence: 60%
“…Furthermore, treatment of the yeast cells with 1,6-hexanediol, a compound used to disrupt weak hydrophobic interactions and disturb LLPS, caused a more uniform redistribution of the Ppb1 protein, further supporting the view of this protein forming biomolecular condensates within living cells [128]. Although the results obtained using 1,6-hexanediol should be interpreted with caution because this alcohol may have potential side effects on protein kinases and protein phosphatases [170], the participation of Pbp1 into the formation of homotypic oligomerization in vivo was further proved using complementary approaches. Thus, co-immunoprecipitation experiments showed that Pbp1 was strongly self-associated in extracts from cells grown in minimum medium, in contrast to cells grown in the presence of glucose.…”
Section: Ataxin-2mentioning
confidence: 65%
“…It is however possible that addition of this alcohol can cause different effects, ranging from alterations of membrane structure to changes in the stability of the structures of globular proteins. Indeed, it has been recently shown that percentages of 1,6‐hexanediol commonly used to disrupt LLPS impact enzymatic activity, for example, inactivating kinases and phosphatases 36 . It is therefore necessary to develop new probes to selectively change the stability of condensates: since moderate (up to 70%) mole fractions of D 2 O can be tolerated by live cells, 37 for example in studies of the rate of protein synthesis in physiology, 38 analysis of how additions of this co‐solvent influence apparent phase separation phenomena in cells may represent a useful tool in this field.…”
Section: Discussionmentioning
confidence: 99%